Occult nasolacrimal duct ectasia in a child with acute sinusitis: clinicopathological considerations and literature review - Giordano, Davide; Gradoni, Paolo; Oretti, Gabriele; Cerasti, Davide; Ferri, Teore (Acta Biomedica Atenei Parmensis, 2015)
Background: Enlargement of the nasolacrimal duct (NLD) in the absence of neoplasm is rare. As there are few reports on this condition in the literature, its pathologic significance and proper management remain unclear. We report a case of asymptomatic NLD enlargement incidentally discovered on high resolution computed tomography scan performed for a complicated acute sinusitis. Methodology: Case report and literature review. Results and conclusions: NLD enlargement, defined as a truly isolated asymptomatic dilatation of the NLD, is rarely encountered. Etiology and clinical significance are unclear although the absence of nasolacrimal pathway or sinonasal disease and radiological findings of bone remodelling suggest that it may be congenital. In such cases, diagnosis may be incidental and based on imaging studies, and the term NLD ectasia seems to be more appropriate to describe this distinct entity. NLD enlargement may favour osteomeatal complex obstruction, thus leading to severe acute sinusitis.